Organise/Curator - Koutsomichalis, Marinos (My University, 2026)
A hybrid open-ended do-it-with-others workshop revolving around experimental making, irrational tonalities, resonant impromptu data scratching, post-digital utopias, and weird speculative artefacts. MADLab (Limassol, CY).